2011
DOI: 10.1016/j.nano.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Micellar nanomedicine of human neuropeptide Y

Abstract: Human neuropeptide Y (NPY) is an important biologics that regulates multitude of physiological functions and could be amenable to therapeutic manipulations in certain disease states. However, rapid (minutes) enzymatic degradation and inactivation of NPY precludes its development as a drug. Accordingly, we determined whether self-association of NPY with biocompatible and biodegradable sterically stabilized phospholipid micelles (SSM) improves its stability and bioactivity. We found that in saline NPY spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Results demonstrated that PP retained its a-helical conformation, activity (when in micelles) and SSM did not hamper peptide interaction with its receptor. Similar studies were conducted by Kuzmis et al to improve the stability and bioactivity of NPY with SSM prepared with DSPE-PEG [2000] [148]. NPY in saline formed large aggregates (557 ± 100 nm) but the mean hydrodynamic diameter of NPY in SSM was monomodal (14 ± 3 nm).…”
Section: Colloidal Delivery Systemssupporting
confidence: 65%
See 1 more Smart Citation
“…Results demonstrated that PP retained its a-helical conformation, activity (when in micelles) and SSM did not hamper peptide interaction with its receptor. Similar studies were conducted by Kuzmis et al to improve the stability and bioactivity of NPY with SSM prepared with DSPE-PEG [2000] [148]. NPY in saline formed large aggregates (557 ± 100 nm) but the mean hydrodynamic diameter of NPY in SSM was monomodal (14 ± 3 nm).…”
Section: Colloidal Delivery Systemssupporting
confidence: 65%
“…Examples of such studies include pancreatic polypeptide (PP), and neuropeptide Y (NPY) loaded micelles [147,148]. Banerjee et al encapsulated an endogenous peptide hormone, PP, in a phospholipid micellar formulation [147].…”
Section: Colloidal Delivery Systemsmentioning
confidence: 99%
“…The formulation of PP associated with SSM (PP-SSM) was prepared based on our previous work with other peptides and SSM (27,28,31). Briefly, weighed quantity of DSPE-PEG 2000 was added to phosphate buffer (pH 6.5, 7.4 or 8.0) or normal saline (pH 4.5 – 7.0), vortexed for 2 minutes, (Thermolyne Maxi Mix II) sonicated for 5 minutes (Bransonic Ultrasonic cleaner) and allowed to equilibrate in the dark for 1 hr at 25°C to form micelles at a concentration of lipid above its CMC.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrophobic drugs are solubilized in the lipid core of the micelles (25,26), while amphiphilic peptide drugs are postulated to reside at the PEG palisade and associate with the micelles as monomers that serve to thwart their aggregate formation (27,28). PEG prevents uptake and rapid clearance of these micelles in vivo by the reticulo-endothelial system and also prevents the interaction of the payload with proteolytic enzymes, thus increasing the biological stability and circulation half-life of small molecule drugs (29,30) or peptides (28,31). Previous studies have demonstrated that these lipid micelles significantly enhance the proteolytic stability and biological half-life of peptides such as vasoactive intestinal peptide (27).…”
Section: Introductionmentioning
confidence: 99%
“…Peptides such as vasoactive intestinal peptide (VIP), glucagon-like peptide 1 [GLP-1(7-36)] and gastric inhibitory peptides, associate most probably with the PEG region of PEGylated micelles, in view of the molecular net charge and relative hydrophilicity/hydrophobicity of these peptide candidates, rather than the more hydrophobic micelle cores as demonstrated in our previous fluorescence emission spectroscopic studies [76]. Micelles stabilize the associated peptides against physical aggregation and hydrolytic degradation in vitro to increase their shelf stability in aqueous media [33,79,80]. When administered in vivo, SSM protects the associated peptides from plasma enzymes inactivation, bringing about enhanced and significantly prolonged biological activities (Fig.…”
Section: Delivery Of Peptide and Protein Drugsmentioning
confidence: 99%